Reactive oxygen and nitrogen species during viral infections. (October 2014) - Molteni, C. G.; Principi, N.; Esposito, S.
Abstract Oxygen and nitrogen radicals are frequently produced during viral infections. These radicals are not only a physiological mechanism for pathogen clearance but also result in many pathological consequences. Low concentrations of radicals can promote viral replication; however, high concentrations of radicals can also inhibit viral replication and are detrimental to the cell due to their mitogenic activity. We reviewed the detailed mechanisms behind oxygen and nitrogen radical production and focused on how viruses induce radical production. In addition, we examined the effects of oxygen and nitrogen radicals on both the virus and host. We also reviewed enzymatic and chemical detoxification mechanisms and recent advances in therapeutic antioxidant applications. Many molecules that modulate the redox balance have yielded promising results in cell and animal models of infection. This encourages their use in clinical practice either alone or with existing therapies. However, since the redox balance also plays an important role in host defence against pathogens, carefully designed clinical trials are needed to assess the therapeutic benefits and secondary effects of these molecules and whether these effects differ between different types of viral infections.